Architexture organisationnelle - Karolina Swiderek (Communication)
In this article, we explore the notion of architexts by examining how an organizational architexture is woven together through a string of architexts produced in response to the requirements listed in normative documents. We will look specifically at the mechanics of the process for deconstructing what is written in paper format and how it is transcribed to digital format. We will adopt a pragmatic interdisciplinary perspective and draw on the constitutive communication of organizations to take a closer look at organizing processes.